Implementasi Esensi Pengelolaan Syariah dalam Mendalami Ruang Lingkup dan Prinsip-prinsip Syariah - Cahyani, Ragil Intan; Al Mu’arrifin, Syaiful Fadlol (Masoem University, 2024)
Islamic financial management refers to the principles of sharia in Islam, which prohibit usury (interest), gharar (deception), maysir (gambling), and investment in industries that are considered haram. These principles cover financing, investment, and business in accordance with Islamic law. In Islamic financial management, there are several principles that must be considered, such as the principles of justice, prudence, and transparency. These principles must be applied in all aspects of financial management, including investment decision-making, risk management, and financial reporting.